Main bacteria that cause foodborne diseases - Ariadna Milena Pessoa da Câmara Flores; Cristiano Barros de Melo (Brazilian Journal of Veterinary Medicine, 2015)
ABSTRACT. Flores A.M.P.C. & Melo C.B. [Main bacteria that cause foodborne diseases.] Principais bactérias causadoras de doenças de origem alimentar. Revista Brasileira de Medicina Veterinária, 37(1):65-72, 2015. Universidade de Brasília, Campus Universitário Darcy Ribeiro, ICC Sul, Asa Norte, Brasília, DF 70910-900, Brasil. E-mail: cristianomelo@unb.br Foodborne diseases are major causes of morbidity, mortality and losses to the public health system. The understanding of the problem is the key to minimize morbidity, mortality and losses to the public health system. Thus, this paper aims to review the main bacteria that cause foodborne diseases.